What challenges lie ahead for improvement programmes in the UK? Lessons from the CINet Continuous Improvement Survey 2003. (5th February 2007) - Readman, Jeff; Bessant, John
The results of the UK Continuous Improvement (CI) Survey 2003 are presented in this paper. Key findings underscore performance improvements and the most effective enabling tools and techniques, which support CI initiatives. The paper concludes that more explorative research is required to, first, distinguish CI from other process improvement activities and, second, to distinguish the different applications of CI in production and non-production activities.